Evaluating the Efficiency of schools in Bogotá and Cundinamarca: a metafrontier analysis. (2020)
The evaluation of educational efficiency has had a long research tra dition identifying determinants in academic performance. This study seeks to determine to what extent the management carried out by the schools to achieve their academic objectives is conditioned by the sector to which they belong, the socioeconomic level of their students, and the technological pieces of equipment. For this purpose, a meta-border analysis with six models is used, applying data envelopment analysis to a population made up of 1.421 schools in Bogotá and Cundinamarca for 2016. The descriptive analysis shows that students by government schools presenting the Saber 11 Test are, on average, 2,4 times reported by non-government schools. The results obtained for the meta-border indicate a general inefficiency level of 16,32%. Inefficiency is reduced to 14,44% when com paring the sector to which the schools belong. Finally, when the sector and the socioeconomic level to which the schools belong are considered, the inefficiency of schools is reduced to 13,24%. The schools that benefited most from this segre gation were the government schools, for which it was possible to determine that up to 30% of their inefficiency is explained by the sector and the socioeconomic level to which they belong. Likewise, it was found that government schools have better computer equipment and therefore are more sensitive to this variable. This leads us to deduce that the government schools would be giving little use to this equipment.